VEHICLE SELECTION OF WASTE COLLECTING SYSTEM IN PAYAKUMBUH WITH TIME MOTION STUDY AND ANALYSIS HIERARCHY PROCESS APPROACH - RAHMANIA (NIM : 25316019), SYIFFA
The waste management system consists of several instruments, one of them is waste collection. Payakumbuh city is a city with an area of 80.43 km2 which has a waste service level of 88% in 2016. In order for the existing garbage collection system to be effective and efficient and to increase the percentage of waste service, it is necessary to select the appropriate vehicles. Vehicles selection of waste collecting system conducted with Time Motion Study approach and Analysis Hierarchy Process. The result of research with Time Motion Study approach shows that the highest waste collection efficiency is owned by tricycles motor amounted to 49,53 kg / minute. The efficiency of waste collection by carts has an average value of 28.02 kg / min and truck has an average value of 36.55 kg / min. The correlation test is conducted to find out the variables that affect the value of waste collection efficiency. Overall, the average value of efficiency is influenced by the variables of collection method. Coleection method in form of without going down from the vehicles and going down from the vehicles. The correlation coefficient of 0.659 and a significance number of 0,000 indicates a strong and significant relationship, where efficiency increases by means of without going down from the vehicles. The result of the research using Analysis Hierarchy Process approach shows that respondent group with consistency ratio ≥75% choose tricycles motor with weight 0,371. The result of the research using 2 approaches with various variations of assessment shows that the most efficient and suitable collection mode to be used in Payakumbuh City is tricycles motor. If the decision-making is based on combining selected alternatives of both variables with assumptions of 30% weight for TMS and 70% for AHP, tricycle motor becomes the chosen alternative with a total weight of 0.405.